Alan Astbury. 27 November 1934—21 July 2014. (9th July 2019) - Keeler, Richard K.; Lefebvre, Michel
Abstract : Alan Astbury worked in the area of accelerator based subatomic physics. Increasing beam energies, intensities and types of available accelerated beams opened scientific windows to new phenomena throughout his career. Exploiting these new beams required new techniques and the use of the latest technology. Alan was always at the forefront of putting these components together into the experiments needed to confirm or reject the latest theoretical advances or clarify conflicting experimental observations. Following his PhD using the synchrocyclotron at the University of Liverpool and a postdoctoral position at Berkeley, he became a staff member at the Rutherford Appleton Laboratory, where he played a central role in the successive experiments with the Nimrod proton synchrotron, the 26 GeV proton synchrotron at CERN and, perhaps most significantly, with the UA1 experiment at CERN that discovered the W and Z particles. Alan moved to Canada in 1983 and made enormous contributions to Canadian science. He was instrumental in building relationships between Canadian scientists and CERN, DESY and SLAC. As director of the Canadian Institute of Particle Physics and then director of the TRIUMF laboratory, he guided subatomic physics policy and planning for two decades. On the international scene, he was president of the International Union of Pure and Applied Physics.